A better method for assessment of hepatic function in hepatocellular carcinoma patients treated with radiofrequency ablation: Usefulness of albumin–bilirubin grade. Issue 3 (2nd August 2017) - Hiraoka, Atsushi; Kumada, Takashi; Hirooka, Masashi; Tsuji, Kunihiko; Itobayashi, Ei; Kariyama, Kazuya; Ishikawa, Toru; Tajiri, Kazuto; Ochi, Hirofumi; Tada, Toshifumi; Toyoda, Hidenori; Nouso, Kazuhiro; et al.
Abstract : Aim: To evaluate the efficacy of the newly proposed albumin–bilirubin (ALBI) grade for therapy selection, clinical features of patients treated with radiofrequency ablation (RFA) were elucidated. Methods: From 2000 to 2015, 1101 patients with HCC (<3 cm, ≤3 tumors) treated with RFA were enrolled, with the following clinical features: 734 men and 367 women; 779 with hepatitis C virus, 153 with hepatitis B virus, 5 with hepatitis C and B, and 164 others; and Child–Pugh classification (CP) A : B ratio of 842:259. Liver damage classification (LD) using the indocyanine green retention rate at 15 min and ALBI‐grade were compared in regard to the prognoses of those patients. Results: Median tumor size was 1.7 cm (interquartile range, 1.4–2.2 cm) and single tumors were found in 802 cases (72.8%) (tumor–node–metastasis stage of the Liver Cancer Study Group of Japan I : II : III = 536:454:111). In the LD‐A group, the number of cases with ALBI‐grade 1, 2, and 3 were 294, 224, and 1, respectively, while those in the LD‐B group were 47, 490, and 12, respectively. In the LD‐C group, 19 and 14 patients were ALBI‐2 and ‐3, respectively. Akaike Information Criterion values for CP, LD‐grade, and ALBI‐grade were 6015.4, 5988.8, and 5990.7, respectively. However, there was no significant difference regarding prognosis between LD‐A/B ( n  = 228) and C ( n  = 31) (median survival time, 4.8 vs. 3.9 years, P  = 0.0818) in CP‐B, whereas a significant difference was observed regarding prognosis for ALBI‐1/2 ( n  = 232) and ALBI‐3 ( n  = 27) (median survival time, 4.8 vs. 2.7 years, P  = 0.0168). Conclusion: Albumin–bilirubin grade showed an assessment ability similar to that of LD‐grade. Furthermore, there was a small improvement in prognosis following RFA in patients with an ALBI‐grade of 3. Although only two serological parameters, albumin and total bilirubin, are used, assessment with ALBI‐grade may be more useful than with LD‐grade for avoiding a non‐beneficial RFA procedure.